Prevalence of Prediabetes in Patients with Acute Coronary Syndrome: A Descriptive Cross-Sectional Study - Karki, Biplave; Ghimire, Jeet; Nepal, Bikash; Mahaseth, Aditya; Sah, Ajit; Pandit, Swapnil; Pandey, Naveen; Shah, Prashant; Karki, Prahlad (Nepalese Heart Journal, 2022)
Background and Aims: Diabetes mellitus is a well recognized risk factor for cardiovascular disease and acute coronary syndrome. It is becoming increasingly clear that pre-diabetic state is also associated with adverse clinical outcomes. However, evidence is limited regarding the prognostic value of 'prediabetes' on the clinical outcome of acute coronary syndrome. So, we aimed to assess the prevalence of prediabetes in acute coronary syndrome patients and its clinical outcome Methods: This was a single center descriptive cross-sectional study to know the prevalence of prediabetes in 115 patients consisting of 71 males and 44 females, admitted with acute coronary syndrome in the Department of Cardiology, B.P. Koirala Institute of Health Sciences, Dharan, Nepal, between August 2020 to July 2021. Results: Based on the definition of 2020 American Diabetic Association, 35 (30.4%) patients were newly diagnosed diabetic, 46 (40%) patients were prediabetic and 34(29.6%) were non-diabetic. Based on HbA1c alone, 26.1% patients were classified as newly diagnosed diabetic patients, 38.3% patients were classified as prediabetic and 35.7% as non-diabetic. Compared with patients without diabetes, patients with prediabetes tended to have a longer hospital stay (p=0.04), higher creatine level (p=0.01) and higher incidence of heart failure (p=0.046). Conclusion: Prediabetes is common in patients presenting with acute coronary syndrome who are not previously known to have diabetes. Further multi-center studies with long term clinical follow-up are needed to draw a firm conclusion regarding the impact of prediabetes on clinical outcome